Desenvolvimento e caracterização de dispositivos eletroluminescentes contendo uma blenda polimérica condutora e Zn2SiO4:Mn - Santos, Emily Caroline Coelho dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Despite the great development of organic and polymeric electroluminescent materials, the large scale commercial application of devices made with these materials seems conditioned to specific cases, mainly due to the high cost and the low durability, in compared to conventional technologies. In this study was produced electroluminescent devices by a process simple, drop casting. Were produced electroluminescent films containing Zn2SiO4:Mn immersed in a conductive polymer blend with different thicknesses. The morphological characteristics of these films were studied by scanning electronic microscopy. These films were used in the manufacture of electroluminescent devices, in which the light emission properties of the developed material were evaluated. The blend was composed of the conductive polymer Poly(o-methoxyaniline), doped with p-toluene sulfonic acid, and an insulating polymer, Poly(vinylidene fluoride) and its copolymer Poly(vinylidene fluoride-cotrifluoroethylene). To this blend was added Zn2SiO4:Mn, thereby forming the composite. A first set of devices was obtained using composites with different weight fraction of polymeric and inorganic phases, which were deposited by drop casting over ITO substrates. Upper electrodes of aluminum were deposited by thermal evaporation. The resulting device architecture was a sandwich type structure ITO/ composite/ Al. A second set of devices was obtained as self-sustaining films using the best composite composition obtained for the device of the first set. ITO electrodes were deposited by RF-Sputtering, in both faces of these films. The AC electrical characterization of the devices was made with impedance spectroscopy measurements, and the DC electrical characterization was performed using a source/ meter unit Keithley 2410. The devices light emission was measured using a photodiode coupled to a digital electrometer, Keithley 6517A. The devices electrooptical characterization showed that the...

Apesar do grande desenvolvimento de materiais eletroluminescentes orgânicos e poliméricos, a aplicação comercial destes em larga escala parece ligada a casos específicos, principalmente devido ao alto custo e a baixa durabilidade, em comparação às atuais tecnologias. Neste trabalho foi proposta a fabricação de um dispositivo eletroluminescente a partir de um simples processo, drop casting. Para isso produziu-se filmes eletroluminescentes de Zn2SiO4:Mn imerso em uma blenda polimérica condutora com diferentes espessuras. As características morfológicas destes filmes foram estudadas por microscopia eletrônica de varredura. Estes filmes foram empregados na fabricação de dispositivos eletroluminescentes, com os quais a propriedade de emissão de luz do material desenvolvido foi avaliada. A blenda foi composta pelo polímero condutor Poli(o-metoxianilina) dopado com ácido p-tolueno sulfônico e um polímero isolante, o Poli(fluoreto de vinilideno) e o seu copolímero Poli(fluoreto de vinilideno-co-trifluoretileno). A esta blenda foi adicionado o Zn2SiO4:Mn, formando assim o compósito. Um primeiro conjunto de dispositivos foi obtido usando compósitos com diferentes frações em massa das fases polimérica e inorgânica, os quais foram depositados por drop casting, sobre substratos de ITO. Eletrodos de alumínio foram depositados por evaporação térmica na face oposta a do ITO. A arquitetura do dispositivo resultante foi uma estrutura sanduíche do tipo ITO/Compósito/Al. Um segundo conjunto de dispositivos autossustentáveis foi produzido utilizando a melhor composição do compósito, determinada na etapa anterior do trabalho. Eletrodos de ITO foram depositados por RF-sputtering, em ambas as faces desses filmes. A caracterização elétrica AC dos dispositivos foi feita com a técnica de espectroscopia de impedância, já a caracterização elétrica DC foi realizada utilizando uma unidade source/meter Keithley 2410. A emissão..
Keywords: Fisica; Eletroluminescencia; Polímetros; Luz - Espalhamento